Efek Antidiabetes Kombinasi Ekstrak Mengkudu (Morinda citrifolia) dan Kunyit (Curcuma longa) pada Tikus yang dibuat Hiperglikemik - Iddahan, Viqi; Sutiningsih, Dwi; Martini, Martini (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: Diabetes Mellitus is a disease characterized by hyperglycemia in a long time can cause the damage of pancreatic beta cells. Morinda citrifolia contains xeronine that can regenerate damaged pancreatic beta cells. While Curcuma longa contains curcumin which acts as an antioxidant will stabilize free radicals so it can inhibit pancreatic beta cell damage and stimulate insulin secretion.Methods: The study aim to analyze the effect of a combination of Morinda Citrifolia and Curcuma Longa in reducing blood glucose levels, increasing body weight and pancreatic histopathology in hyperglycemic mice. This type of research is an experiment with the Post Test Only Control Group. A total of  25 mice were divided into 5 groups namely PI (250 mg/dL), PII (500 mg/dL), PIII (750 mg/dL), K(+), and K(-). Blood glucose level was observed for 21 days followed by observation of pancreatic histopathology.Result: The results showed the percentage of glucose blood reduction occurred in the PI group (56.11%) and significantly different from negative controls (35.05%). There was no difference in body weight (p=0.7) and number of langerhans islet (p=0.360) in all treatment groups. The diameter of the Langerhans islet of the PI group (200.8 μm) was significantly different from the negative control (114.8 μm). (p<0.05Conclusion : The combination of Morinda citrifolia and Curcuma longa extract can reduce blood glucose levels and increase body weight but not be able to optimally repair pancreatic islet damage.